Penentuan Harga Pokok Produksi Banten Pawiwahan Pada Pedagang Banten Di Kota Singaraja, Bali - Datu, Santa Tifanny Margaretha; Musmini, Lucy Sri (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2021)
This study aims to determine (1) the method used by Mr. Jro Mangku Sabda in determining the cost of goods, (2) how to calculate the cost of goods manufactured according to the accounting method. This study uses qualitative research with ethonographic research type. The data collection technique is done by observing, interviewing and also studying the documentation. The object of this research is the determination of the cost of production of Banten Pawiwahan for Banten traders in Singaraja City, Bali. The results of this study indicate that 1) The method used by Jro Mangku Sabda is still using the simple method, 2) The method of calculating the cost of production is in accordance with the accounting method, namely by using the full costing method. The calculation of the cost of goods according to the company is more than the full costing method and results in a difference of Rp. 246,000. The difference occurs because the cost treatment in the calculation of direct labor costs and factory overhead costs is different. The difference in the calculation of the element of direct labor costs is Rp. 90,000. For factory overhead costs, the inter-company calculation method with the full costing method is Rp. 156,000.